PENGARUH OLAHRAGA PAGI TERHADAP KESEHATAN ANAK TAMAN KANAK-KANAK - Fitriyani, Lulu Hikmah; Handayani, Fitri; Nafiqoh, Heni (IKIP Siliwangi, 2018)
The main issues of this research is how the influence of morning exercise on the health of kindergarden children. The purpose of this study was to determine whether there is a significant influence between morning exercise and children health. The research method used is quasi experimental research method. The sample of the research is 36 male children of kindergarden Pangkalan Kabupaten Bandung. The results showed that there was a significant influence between morning exercise and the health of kindergarden childrenas many as 20 children. Morning exercise needs to be done consistently before beginning classroom learning. There needs to be a more adequate increase in sport facilities and infrastructure in kindergarden.